Mental health and care homes - Dening, Tom; Milne, Alisoun (Oxford University Press, 2011)
The care home sector is large, with over 400 000 residents in the UK and a similar number employed within the homes. It is therefore an area of considerable economic importance. Care home residents are often very old, and many have multiple physical and mental health needs, meaning that their care poses particular challenges. They are also a distinctly and profoundly marginalised group who are often invisible in the wider debates on quality of care including those about care homes. Mental Health and Care Homes is a coherent and evidence-based text exploring these issues. Bringing together both.